Developing the Use of Google Translate to Enhance Student’s Ability to Translate Acehnese Proverb - Allif Syahputra Bania; Berlin Sibarani; Isli Iriani Indiah Pane; Aprilza Aswani (Talenta Publisher, 2026)
One of the uniqueness of Aceh region that describes the image of local culture from the original heritage of the ancestors is the Acehnese proverb. However, it is unfortunate that Acehnese proverbs are now fading to extinction. Acehnese proverbs as an oral cultural heritage must be preserved in this digital era, this study wants to find out the quality of the translation of Acehnese proverbs via Google Translate and also wants to find out the understanding of the Acehnese people towards Acehnese proverbs via Google Translate. This study uses a descriptive-qualitative approach. The test method is used to determine the quality of the translation and questionnaires are distributed to 100 respondents who master Acehnese and English to find out the understanding of Acehnese proverbs with the help of Google Translate. The data source is six Acehnese proverbs with two lines. Analysis of translation quality based on the aspects of accuracy, acceptability, and readability. The results obtained that the translation of Acehnese proverbs into English as an international language via Google Translate is not good. The understanding of the Acehnese via Google Translate is not satisfaction because the translation feels strange because it is inaccurate, unusual, and not easy to read